Comparative Analysis of Silver Generated Fixer of Saturated with Electrolytic Method and Deposition Of NaOH 5 M - Sri Mulyati; Jeffri Ardiyanto; Ahkmad Haris Sulistiyadi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
The purpose of this study was to determine the weight of the silver produced from silver recovery process using electrolysis and chemical deposition method with which NaOH 5 M. As well as to determine the method most widely produced silver from both methods. This research is an experimental study. Data collection was performed on material that has been saturated with fixer electrolysis method and precipitation with NaOH 5 M. Fixer solution that has been saturated by 20 liters divided by two. Furthermore, each volume by 10 liters silver recovery process performed by the method of electrolysis and precipitation with NaOH 5 M. The results showed that the silver recovery by electrolysis method produces silver as much as 29 grams, while silver recovery with NaOH 5 M resulted in the deposition of silver as much as 27 grams. Of both methods are the most widely produced silver is a method of electrolysis. Besides electrolysis method has the advantage of faster process, more practical, in generating pure silver is ready for sale. But it has the disadvantage expensive appliance. While the deposition method is cheaper, long process, longer chemical contamination and dangerous, impractical, drying takes a long time to do a new purification by combustion (burning with welding tools).